2020
DOI: 10.12688/f1000research.25891.1
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioners and physician assistants working in ambulance care: A systematic review

Abstract: Background: This review aims to describe the activities of nurse practitioners (NPs) and physician assistants (PAs) working in ambulance care, and the effect of these activities on patient outcomes, process of care, provider outcomes, and costs. Methods: PubMed, MEDLINE (EBSCO), EMBASE (OVID), Web of Science, the Cochrane Library (Cochrane Database of Systematic Review), CINAHL Plus, and the reference lists of the included articles were systematically searched in November 2019. All types of peer-reviewed desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Future studies should examine the variance in prescribing safety and patient outcomes between NPs as sole PCPs and NPs in a team-based primary care model. A comparison of NPs and physician assistants working in ambulatory care is needed 38…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should examine the variance in prescribing safety and patient outcomes between NPs as sole PCPs and NPs in a team-based primary care model. A comparison of NPs and physician assistants working in ambulatory care is needed 38…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the effect of the PA on quality of ambulance care should be further assessed. Future research on the impact of the PA within ambulance care should be assessed by using the six dimensions of quality of healthcare: (1) effectiveness, (2) efficiency, (3) patient safety, (4) accessibility, (5) timeliness and ( 6) target population directed 15 . The effects on these dimensions should be measured in all phases of the ambulance process, from initial call and dispatch triage, to handover or referral.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of the PA in ambulance care, little is known about the effects. A recent systematic review showed limited available evidence on the introduction of master's level educated professionals in ambulance care, with lacking evidence on patient outcomes 15 . This underpins the need for further research on effectiveness, efficiency, patient safety, and accessibility of the introduction of PAs in ambulance care.…”
Section: Introductionmentioning
confidence: 99%
“…Disagreements between reviewers were noted for some elements of the AMSTAR 2 assessment tool (see Discussion). Nineteen studies were assessed to be at low risk of bias with four or fewer criteria that were not met and no critical domains missing [11,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Four studies were deemed to be at high risk of bias [46][47][48][49].…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%